Mega roles of microRNAs in regulation of skeletal muscle health and disease - Sharma, Mridula; Juvvuna, Prasanna Kumar; Kukreti, Himani; McFarlane, Craig (Frontiers in Physiology, 2014)
Skeletal muscle is a dynamic tissue with remarkable plasticity. Skeletal muscle growth and regeneration are highly organized processes thus it is not surprising that a high degree of complexity exists in the regulation of these processes. Recent discovery of non-coding microRNAs (miRNAs) has prompted extensive research in understanding the roles of these molecules in skeletal muscle. Research so far shows that miRNAs play a very significant role at every aspect of muscle biology. Besides muscle growth, development and regeneration miRNAs are also involved in the pathology of muscle diseases and metabolism. In this review, recent advancements in miRNA function during myogenesis, exercise, atrophy, aging and dystrophy are discussed.